(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
This article focuses on the need to conduct specific scientific research on improving the legal culture of young people today, making the issue of increasing legal awareness, legal culture, and the role of civil society institutions in this process a priority direction of state legal policy, an important criterion in the implementation of democratic principles.